Pregnancy outcome following various doses of antioxidants such as Vitamin E supplementation – current state of knowledge - Skalska-Dziobek, Nina; Małagocka, Weronika; Chybowska, Karolina; Rozpłoch-Sapa, Maria; Orłowski, Mateusz; Naruszewicz, Maria; Midro, Aleksandra; Cetnarowski, Przemysław; Zagórski, Karol; Kozik, Mateusz (Quality in Sport, 2024)
Introduction and purpose: Vitamin E is an antioxidant substance. It has been noted that the pathomechanism of many diseases in pregnancy is rooted in oxidative stress. Much of them have an incompletely understood mechanism, and thus treatment is not as effective. Vitamin E is a readily available and important antioxidant. It is reasonable to investigate whether there are links between supplementation with this vitamin and improved outcomes of conditions in pregnant women. Conditions such as preeclampsia (also in a group of women with type 1 diabetes), preterm premature rupture of membranes, spontaneous preterm birth, respiratory diseases were considered. Material and method: The literature was reviewed in the Pubmed database, GoogleScholar, in the Via Medica journal database, the positions of the Polish gynecological society with the use of keywords. State of knowledge: According to the cited studies, routine use of vitamin E in combination with other supplements has no discernible benefit. No differences were found in groups taking antioxidants from placebo groups in the context of pregnancy diseases. There were side effects of supplementation and for this reason supplementation with this antioxidant should not be ordered without clear indications. Conclusions: The information gathered does not indicate the usefulness of vitamin E supplementation in pregnancy. The issue of the use of antioxidants in the fight against diseases that occur during pregnancy requires further research.